Surviving in the Digital Space: Digital Literacy of Syrian Immigrants in Turkey - Serkan Bayrakcı; Haldun Narmanlıoğlu (Türkiye İletişim Araştırmaları Dergisi)
Turkey is one of the countries hosting the largest number of Syrian immigrants in the world. Integrationof Syrian immigrants is one of the problems Turkey has to overcome. Many studies around the worldshow that digital communication tools can be used effectively by immigrants in many integration processessuch as language learning, learning about culture and socialization. In this study, which was carried outas a project of The Scientific And Technological Research Council of Türkiye (TÜBİTAK), we aimed todetermine the digital literacy levels of Syrian immigrants, which is a prerequisite for their integration byusing digital tools. We applied a digital literacy scale adapted to Arabic to Syrian immigrants. The study,which was conducted both online and face-to-face, investigated the general digital literacy status of Syrianimmigrants and their digital literacy levels according to variables such as gender, age, education level,income level, access to the internet, and Turkish citizenship status. Both at the general level and at the levelof all variables, the digital literacy of Syrian immigrants was determined to be “Below Average / Weak”.Especially in European countries, public policies have started to be established to increase the digital literacylevels of isolated groups such as immigrants. In order to overcome the immigrant integration problem inTurkey through digital communication, public policies should be established to increase the digital literacylevels of immigrants.